Assessing the effects of trade openness on sustainable development: Evidence from India - Mehraj Ahmad Sheikh; Mushtaq Ahmad Malik; Rana Zehra Masood (Asian Journal of Sustainability and Social Responsibility (AJSSR), 2020)
Over the years, world market is integrating at much faster pace through increasing trade openness. Not being an unmixed blessing, consistent efforts have been made to examine impact of trade openness on economic, environmental and social welfare. This study is an attempt to empirically examine the implications of trade openness on sustainable development in India since liberalization policy 1991. We used the Autoregressive Distributed Lag (ARDL) model to test the relationship between sustainable development and trade openness along with other control variables that are supposed to affect sustainable development. The results established supports the opinion of environmentalists. The empirical results are contrary to the conventionally held belief, indicating that trade shares a negative correlation with green GDP growth and positive correlation with gap between conventional GDP and green GDP. These findings support the arguments that trade openness tend to be both distorting and detrimental to the future generations.
Keywords: 650; Trade openness; Genuine savings; Sustainable development; ARDL approach